2000
DOI: 10.1088/0957-0233/11/5/316
|View full text |Cite
|
Sign up to set email alerts
|

Multiple harmonic compensation of Langmuir probes in rf discharges

Abstract: We report on the use of an active Langmuir probe with three-harmonic compensation to diagnose rf discharge plasmas driven at 13.56 MHz. The plasma generates many harmonics on the fundamental, the first few being strongest. This gives a multi-harmonic rf voltage across the probe sheath that is removed by applying a rf signal to the probe that is matched both in amplitude and in phase for each harmonic. The probe I-V characteristic can then be analysed using dc theory. We show here that only when the rf harmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 11 publications
(9 reference statements)
1
37
0
Order By: Relevance
“…8,10 We control the ion energy at the substrate by applying an RF potential to the substrate which nulls the RF sheath potential. To reach the minimum ion energy (floating potential), the RF voltage applied must be matched in both phase and amplitude to the RF potentials already present in the sheath 11 that no current, and hence no power, flows into the plasma. Once this condition is satisfied, the bulk plasma is unperturbed and independent control of the ion energy is achieved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10 We control the ion energy at the substrate by applying an RF potential to the substrate which nulls the RF sheath potential. To reach the minimum ion energy (floating potential), the RF voltage applied must be matched in both phase and amplitude to the RF potentials already present in the sheath 11 that no current, and hence no power, flows into the plasma. Once this condition is satisfied, the bulk plasma is unperturbed and independent control of the ion energy is achieved.…”
Section: Methodsmentioning
confidence: 99%
“…The RF bias potential is provided by a separate power supply, which amplifies a signal taken from an electronic module. The module uses a phase reference signal, taken from a pickup electrode, to provide an input into the amplifier which can be varied in both phase and amplitude with respect to the pickup . In this way, it is possible to provide a voltage to the substrate which is matched to the RF potential in the plasma, for the 13.56 MHz fundamental and the first two harmonics at 27.1 and 40.7 MHz.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, various RF compensation techniques with active or passive filter designs have been developed over the last decades. In practice, however, it is often extremely difficult to achieve sufficient RF compensation for various plasma conditions 10 and it has been shown that already small RF distortions can lead to highly erroneous EEDFs especially near zero electron energy [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation described above of such disturbed characteristics gives incorrect plasma parameters. To avoid this problem the probe tip is forced to follow the varying plasma potential either by driving the probe with an rf-voltage [4,5], or by increasing the impedance between probe and ground [6].…”
Section: Introductionmentioning
confidence: 99%